2018
DOI: 10.1186/s12877-018-0891-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in elderly people is associated with diet, wellbeing, health status, social support and physical functioning- a HUNT3 study

Abstract: BackgroundThe increasing proportion of people growing old, demands expanded knowledge of how people can experience successful aging. Having a good life while growing old is dependent on several factors such as nutrition, physical health, the ability to perform activities of daily living, lifestyle and psychological health. Furthermore, unhealthy food intake is found to be a modifiable risk factor for depression in elderly people. To promote elderly’s health and wellbeing, the influence of nutrition, lifestyle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
37
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 34 publications
7
37
2
1
Order By: Relevance
“…The findings also point out gender differences in food preferences [37,49]. Older females seem to have a healthier diet pattern than older males, and therefore, they are less psychologically distressed.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The findings also point out gender differences in food preferences [37,49]. Older females seem to have a healthier diet pattern than older males, and therefore, they are less psychologically distressed.…”
Section: Discussionmentioning
confidence: 67%
“…The authors altogether identified six original articles on the research topic. Only two studies [35,36] were randomized controlled trials (RCT) and four studies [37][38][39][40] were cross-sectional studies. Three of these studies originated in Asia (Malaysia, Japan, and South Korea) [36,[39][40], one in Australia [35], and two in Europe (Croatia, Norway) [37,38].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, American elderly people, for example, even at a very old age, presented good mental health, autonomy and resilience, although they had signi cant physical limitations and de cits in social interaction (32) , two of the aspects that favoured the Portuguese in our research. Other authors also praise how much the preservation of the physical and social aspects prevents mental suffering (33) . However, the social role functioning domain did not show signi cant performance among the levels of depression in Brazilians.…”
Section: Discussionmentioning
confidence: 99%